Indonesia's Geostrategic Position in Global and Regional Politics: Government Preparation - Solehudin, Rd. Heri (CV. Bimbingan Belajar Assyfa, 2023)
The People's Republic of China (PRC) and the United States (US) continue to compete for power and influence in Asia, especially in Southeast Asia. This region, united in the ASEAN Community Agreement, is very important in understanding the pressures on Indonesia's geostrategic development. Failure to anticipate these pressures could endanger Indonesia's national interests and hinder the achievement of its goals and aspirations. Even though the current strategic environment is dynamic, comprehensive research on development strategies in Indonesia's geostrategic landscape is still lacking. Therefore, it is very important for the Indonesian government to actively maintain and improve its geostrategic position in both global and regional politics. This study emphasizes the need for significant consideration of these efforts in national policy-making to effectively safeguard Indonesia's national interests. A comprehensive literature review was conducted over the past decade using the “PoP” application, which combines data from various databases such as PubMed, ABI/INFORM, EBSCOhost, Emerald, Google Scholar, ScienceDirect, ProQuest, Web of Science, and ERIC. This study explores important concepts such as “global politics”, “ASEAN Community”, “political development”, “political dynamics”, and “geostrategic conditions”. It also addresses challenges posed by inadequate infrastructure and limited accessibility. This research provides a comprehensive survey of the existing literature on global and regional political development processes, emphasizing the need for long-term studies of impacts, distribution tactics, and research methodologies. By predicting vulnerabilities in each National Resilience Gatra based on global and regional political dynamics, this study underscores the importance of safeguarding national interests and achieving Indonesia's ideals. Further research is essential to fill existing gaps and support Indonesia in navigating the complexity of the evolving geopolitical landscape.